Pole Image in the Light of Media Texts Created in the Internet Space by Residents of Neighbouring Countries - Hartenberger, Marta (Vilnius University Open Series, 2020)
The issue of national stereotypes requires, in the situation of dynamic changes in Europe and in the world, to update and consider new sources. A new area for tracking changes in the mutual perception of neighbouring nations are the texts of media culture, combining verbal and visual code. In the article, I elaborate on the legitimacy of using such intersemiotic messages, such as memes, demotivators, posters, advertisements, to study stereotypes. The Internet stereotype of a Pole functions on two levels, language and imagination, therefore it is a continuation of the national stereotype in a changed form.